STRATEGI PENERJEMAHAN METAFORA LEKSIKON BAYANGAN PADA NOVEL KOKORO KARYA NATSUME SOSEKI - Wiyatasari, S.S., M.Hum., Reny (KIRYOKU, 2021)
(The Translation Strategies of Shadow Lexicon Metaphors in Kokoro Novel by Natsume Soseki) This research aims to describe the translation strategies used by the translator of Kokoro Novel to translate metaphors with kage ‘shadow’ lexicon. The source of this research are Kokoro, a novel by a famous Japanese writer Natsume Soseki, and also Rahasia Hati, the translation version of his work in Indonesian language by Hartojo Andangdjaja. The research methodology relies on “Simak” method and “Catat” technique for providing the data. The method of providing data used is the listening method and the note-taking technique, while the intralingual and extra lingual matching methods are used to analyze the data (Mahsun, 2005). As for the theoretical framework, it relies on Nakamura’s classification of the nature category in metaphorical expression (1979) and Larson’s strategies of metaphor translation theory (1988). The result shows there are 9 metaphorical data with kage ‘shadow’ lexicon. As for the translation strategies, 5 data are using“M-M” strategy and 4 data are using “M-Nonfiguratif” strategy.  Keywords: strategies of metaphor translation, lexicon, Natsume Soseki.